Washington D.C. 27 Stat. 116 (1892) - (:unkn) unknown (My University, 1892)
That it shall not be lawful for any person or persons within the District of Columbia, to have concealed about their person any deadly or dangerous weapons, such as daggers, air-guns, pistols, bowie-knives, dirk knives or dirks, blackjacks, razors, razor blades, sword canes, slung shot, brass or other metal knuckles.That it shall not be lawful for any person or persons within the District of Columbia to carry openly any such weapons as hereinbefore described with intent to unlawfully use the same, and any person or persons violating either of these sections shall be deemed guilty of a misdemeanor. That any person or persons who shall, within the District of Columbia, sell, barter, hire, lend or give to any minor under the age of twenty-one years any such weapon as hereinbefore described shall be deemed guilty of a misdemeanor
Keywords: CARRY; TRANSFER - MINORS